Rediscovering Frescoes of Archangel Michael Church in Skovorodsky Monastery of Novgorod the Great: Archival Documents and Field Research - Shapovalova, Aleksandra N. (Actual Problems of Theory and History of Art, 2014)
The present article provides an overview of the academic literature on the history of the fresco painting ensemble of Archangel Michael church in the Skovorodsky monastery of Novgorod the Great. This monument belongs to the epoch of the late 14th – early 15th century — a turning point for the Medieval Rus-sian art. Being ruined during the World War ΙΙ, it still remains insufficiently studied. Some specific features of its style and iconography nowadays require detailed consideration. In addition to the overview of major academic works on this monument the article explores the archival materials of its restorers, who discovered Skovorodsky fresco ensemble in 1937–1938 and the results of the Novgorod State Museum archeological expedition of the 2000–2010’s.